Diffusion bonding between high chromium white iron and low carbon steel - Eroglu, M.; Kurt, B. (Maney Publishing, 2007)
In the present study, a high chromium white iron was diffusion bonded to a low carbon steel. The effects of bonding temperature and holding time at the reached temperature on microstructural developments across the joint region were investigated. After diffusion bonding, microstructural analysis including metallographical examination, energy dispersive X-ray (EDX), wavelength dispersive X-ray (WDX), microhardness measurements and shear strength tests were performed. The results showed that bonding temperature with holding time was effective on the width of the diffusion zone that affected the shear strength of the bonds. As a result, from the microstructural observations, EDX and WDX analysis, microhardness measurements and shear strength tests, it was concluded that a high temperature with a long holding time must be used in the diffusion bonding of high chromium white cast irons to low carbon steels.
Keywords: high chromium white iron; diffusion bonding; AISI 1020 steel; microstructure; hardness